STRENGTHENING THE POSITION OF ATTORNEY IN THE 1945 CONSTITUTION OF THE REPUBLIC OF INDONESIA - Muhammad Juriko Wibisono; Amancik Amancik; Ardilafiza Ardilafiza (Bengkoelen Justice : Jurnal Ilmu Hukum, 2021)
The arrangement of the Attorney institution of the Republic of Indonesia in the 1945 Constitution is less clear and less detailed about its position as well as its authority in law enforcement. Departing from the description of the weakness of the Attorney of the Republic of Indonesia’s position above, it is necessary to place the Attorney of the Republic of Indonesia proportionally in order to be autonomous and independent in the perspective of the rule of law theory and the power sharing theory. Based on the results of the study, it can be concluded that the position of Attorney in the 1945 Constitution which was attached in the executive domain had caused a lot of debate. The debate was focused on whether it was a right choice to practically put the Attorney as a law enforcement institution in Executive domain where it should had been legally put in judiciary domain. Furthermore, strengthening the position of Attorney in the 1945 Constitution can be done though the fifth amendment of the 1945 Constitution, therefore the adjustment of the Attorney position must be explicitly stated in the institutions within the environment of judicial power accompanied by its authority.